108k views
2 votes
Write the following equation as a balanced ionic equation

Zn(s) + Pb(NO₃)₂ (aq) --> Zn(NO₃)₂ (aq) + Pb (s)

I don't understand how to write it in the ionic equation form! Thanks!

User Benicamera
by
6.1k points

1 Answer

4 votes

Hey there!:

Molecular equation is:

Zn (s) + Pb(NO3)2 (aq) --> Zn(NO3)2 (aq) + Pb (s)

To get complete ionic equation, break aqueous components into respective ions,so the complete ionic equation is

Zn (s) + Pb²⁺ (aq) + 2 NO³⁻(aq) --> Zn²⁺ (aq) + 2 NO³⁻ (aq) + Pb (s)

To get net ionic equation, remove the common ions from both sides

So, the net ionic equation is:

Zn (s) + Pb²⁺ (aq) --> Zn²⁺ (aq) + Pb (s)

Hope that helps!

User Ahmed Waheed
by
7.1k points